Africa's Pulse, No. 20, October 2019 : An Analysis of Issues Shaping Africa’s Economic Future - Calderon, Cesar; Kambou, Gerard; Cantu Canales, Catalina; Korman, Vijdan; Kubota, Megumi (Washington, DC: World Bank, 2019)
Africa's Pulse is a biannual publication containing an analysis of the near-term macroeconomic outlook for the region. Each issue also includes a section focusing upon a topic that represents a particular development challenge for the continent. It is produced by the Office of the Chief Economist for the Africa Region of the World Bank.